The Representation of the Concept “Home/ Fatherland” (Based on Russian and Armenian Proverbs) - Nina Karapetovna Gasparian (Rusistika (Moskva. Online), 2018)
Linguistic and cultural analysis of the basic concepts of human external and internal world can reveal national character, national ideas, various cultural ideals reflected in these concepts. The concept “Home/Fatherland” is one of the key concepts in the worldview of Russians and Armenians. The author analyses the concept “Home/Fatherland” as a means of representing reality in national consciousness comparing two linguistic pictures of the world. We know that a concept contains important cultural information, concealing its direct meaning in a linguistic unit. The article presents the results of comparative linguistic and cultural analysis of the concept “Home/Fatherland” on the material of the two languages paremiology. The proverbs and sayings gave the author the opportunity to identify the similarities and differences in Russian and Armenian perception of the Home/Fatherland and to determine national and cultural specificity of the concept “Home/Fatherland”.